Competências de soldado: relações de gênero e formação profissional na Polícia Militar. - Nascimento, Iris Oliveira do (2013)
This study sought to investigate, with focus on gender relations, the gender (self) representations of male and female students submitted to the curriculum of the Soldier Training Program at Paraiba's Military Police (Technical Course in Preventive Police), developed by CFAP(Police Training Centre) located in the Education Center of Paraiba Military Police, in João Pessoa, during the period of September 19, 2011 to July 26, 2012. For this purpose, the research which is characterized as exploratory and descriptive social research merged qualitative and quantitative methods. The data collection used both documentary and empirical approaches. The former aimed to raise the official guidelines for the inclusion of gender articulating the results with the focused curriculum. The latter used survey questionnaires applied to a sample of students submitted to the curriculum, intending thus to identify how they associate representations and self representations of gender to the technical, professional and personal competencies described in the official curriculum. The documentary analysis pointed out that the formal curriculum current version was updated in 2005 to suit he orientations from SENASP through the National Curriculum Matrix; however, the curriculum on tents are still lacking with regard to the Thematic Area relative to diversity, where gender issues are included. The data analysis from the questionnaire showed that gender (self) representations of students are still clearly marked by a sexual and historic division of tasks, distinguishing gender roles corresponding to men and women in the exercise of police activities. The data analysis showed that the military organizational culture still identifies the military habitus only with masculinity, according to traditional gender dichotomies, therefore, it excludes female identity inside the police institution. The results suggest that the absence of a gender inclusive curriculum contributes to reproduce gender inequalities that are reflected in the delimitation of the roles performed by male and female soldiers in their professional activities.